Solid waste management simulation model in a Peruvian University - et. al., Anwar Julio Yarin Achachagua, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of the article is to demonstrate the benefits of implementing the simulation model of a comprehensive solid waste control at a Peruvian University and be recognized in our country as the first university that contributes to environmental benefits and at the same time generate income with the commercialization of solid waste for the benefit of the University, through defined strategies. The model was defined by the diagram of activities and programmed in Arena. The model integrates different components such as simulation time, location, types and amount of waste. It is concluded that the programming model for solid waste management benefits significantly in the amount of solid waste in a Peruvian university. Finally, we made a comparison of two possible scenarios, one of which contemplates the alternative of use-benefit of waste, while the other scenario maintains the tendency to collect all waste for disposal.